Legal Framework for Inclusive Digital Transformation: Ombudsman Role in Ensuring Citizens Rights (Open Society Conference, 2025)
Digital transformation in public service delivery has become a central pillar of Indonesia’s national bureaucratic reform, promoting efficiency, transparency, and accountability. However, the acceleration of digitalization has not been adequately accompanied by legal instruments that explicitly uphold the principle of inclusivity, resulting in potential digital exclusion of vulnerable groups, including remote communities, the elderly, and persons with disabilities. This study identifies a legal vacuum regarding the absence of a clear, operational, and enforceable regulatory framework that mandates public service providers to guarantee digital accessibility and establish robust accountability mechanisms in the event of rights violations. Employing a normative juridical method, the research adopts statutory and conceptual approaches, and applies systematic and teleological interpretations of relevant legal norms—primarily Law No. 25/2009 on Public Services and Law No. 37/2008 on the Indonesian Ombudsman. The analysis reveals the strategic oversight function of the Ombudsman in protecting citizens’ rights within digital public service ecosystems through: (1) handling and investigating reports of maladministration involving electronic-based systems; (2) initiating investigations into discriminatory practices or restrictions on digital access; and (3) issuing corrective recommendations to public service providers utilizing technology in a manner that undermines the principle of equality. The study concludes with a call for the reformulation of a binding legal framework to ensure that digital transformation in public services is conducted fairly and inclusively. Furthermore, it underscores the need to strengthen the institutional capacity and mandate of the Ombudsman as an independent supervisory authority within the national digital governance architecture.